miR-731 modulates the zebrafish heart morphogenesis via targeting Calcineurin/Nfatc3a pathway - Huang, Yan; Wang, Wei-Feng; Huang, Chun-Xiao; Li, Xuan-Hui; Liu, Hong; Wang, Huan-Ling (Biochimica et biophysica acta. General subjects, 2022)
Zebrafish miR-731 is orthologous of human miR-425, which has been demonstrated to have cardio-protective roles by a variety of mechanisms. The miR-731 morphants show pericardium enlargement, and many DEGs (differentially expressed genes) are enriched in ‘Cardiac muscle contraction’ and ‘Calcium signaling pathway’, implying that miR-731 plays a potential role in heart function and development. However，the in vivo physiological role of miR-731 in the heart needs to be fully defined. Zebrafish miR-731 morphants were generated by morpholino knockdown, and miR-731 knockout zebrafish was generated by CRISRP/Cas9. We observed cardiac morphogenesis based on whole-mount in situ hybridization. Furthermore, RNA-seq and qRT-PCR were used to elucidate the molecular mechanism and analyze the gene expression. Double luciferase verification and Western blot were used to verify the target gene. The depletion of miR-731 in zebrafish embryos caused the deficiency of cardiac development and function, which was associated with reduced heart rate, ventricular enlargement and heart looping disorder. In addition, mechanistic study demonstrated that Calcineurin/Nfatc3a signaling involved in miR-731 depletion induced abnormal cardiac function and developmental defects. MiR-731 regulates cardiac function and morphogenesis through Calcineurin/Nfatc3a signaling. Our studies highlight the potential importance of miR-731 in cardiac development. •Zebrafish miR-731−/− knockout mutant was generated.•nfatc3a is a direct target of miR-731.•Calcineurin/Nfatc3a signaling is involved in miR-731 depletion induced heart morphogenesis.